Android apps for absolute beginners - Jackson, Wallace (Apress Distributed to the book trade by Springer Science + Business Media, 2011)
Anybody can start building simple apps for the Android platform, and this book will show you how! Android Apps for Absolute Beginners takes you through the process of getting your first Android applications up and running using plain English and practical examples. It cuts through the fog of jargon and mystery that surrounds Android application development, and gives you simple, step-by-step instructions to get you started. Teaches Android application development in language anyone can understand, giving you the best possible start in Android development; Provides simple, step-by-step examples that make learning easy, allowing you to pick up the concepts without fuss; Offers clear code descriptions and layout so that you can get your apps running as soon as possible.